2018
DOI: 10.26480/ees.02.2018.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness and Potentials of Two Flowering Roadside Hedgerows, Turnera Ulmifolia and Melastoma Malabathricum as Beneficial Plants for Insects

Abstract: Beneficial flowering plants play a vital role in attracting beneficial insects such as parasitoid that controls insect pests. In order to evaluate the effectiveness of two species of flowering plants as beneficial hedgerow plants, we identify insects communities of T. ulmifolia and M. malabathricum, which generally grown on roadside. We also compared the insects community of both plants based on time of the day. A total of 5,029 insect individuals were collected through three sampling occasions from five sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This greater abundance of nectar sources is also likely to contribute to the higher density of butterflies in Edge habitats and the higher incidence of nectar feeding we recorded. Larvae of Acraea terpsicore , one of the most common butterfly species we observed, also feed on Turnera ulmifolia , further explaining the higher counts of this species in Edge habitats (Abdullah and Rahim, 2018). Borreria latifolia (Subedi et al 2020), a known food source for Ypthima , spp.…”
Section: Discussionmentioning
confidence: 71%
“…This greater abundance of nectar sources is also likely to contribute to the higher density of butterflies in Edge habitats and the higher incidence of nectar feeding we recorded. Larvae of Acraea terpsicore , one of the most common butterfly species we observed, also feed on Turnera ulmifolia , further explaining the higher counts of this species in Edge habitats (Abdullah and Rahim, 2018). Borreria latifolia (Subedi et al 2020), a known food source for Ypthima , spp.…”
Section: Discussionmentioning
confidence: 71%
“…and Tachysurus in the Arabian Sea was well predicted based on the data of sea surface temperature (SST), chlorophyll a (Chl a) concentration, photosynthetically active radiation (PRA) and sea level anomalies (SLA) in the study of Solanki (2017). The interaction between upwelling index, year and latitude had a great influence on the spatial distribution of sardines in Mauritanian waters (Bacha et al, 2017;Abdullah and Rahim, 2018). Wang et al (2018) reported that prey density, water depth, bottom water temperature and distance to shore had a great influence on the distribution of Chinese white dolphin in western Pearl River Estuary.…”
Section: Introductionmentioning
confidence: 87%
“…Others noted that criteria would vary depending on the regional circumstances and should include, inter alia, biological productivity and/or diversity (Ban et al, 2017;Rahim et al, 2018). In addition, countries called for establishing MPAs in vulnerable areas and important areas for certain species (Cabral et al, 2017;Abdullah and Rahim, 2018). The positions of countries on this issue were dispersed, and the main dispute lies in which scientific criteria should be introduced into the ILBI.…”
Section: The Selection Criteria For Mpas Are Still Not Clearmentioning
confidence: 99%